Litigation risk and innovation portfolio: analysing firms’ direction of innovation - Okutue, Glory (2024)
This study examines the impact of litigation risk on corporate innovation, using the 2006 eBay v. MercExchange Supreme Court decision as a natural experiment. By employing a difference-in-differences approach and leveraging firm-level variation in exposure to patent litigation, this dissertation analyses how firms adjust their innovation strategies in response to reduced litigation risk. The ruling, which altered the enforcement of patent rights, serves as the basis for this analysis. The findings of the study reveal that the ruling significantly increased overall patenting activity and the number of patents in existing technological fields. However, firms remained cautious about exploring new fields. The study also highlights variations based on firm size, with larger firms more likely to increase patents filed in familiar domains while smaller firms focused on reinforcing their core technologies without significantly increasing their number of patents. These results provide important insights into the complex relationship between legal environments and innovation strategies, suggesting that changes in patent enforcement may have differential impacts based on firm characteristics.